Fine Needle Aspiration Cytology (FNAC) in Thyroid Gland Lesions, How Accurate is it? A Correlation with Histopathology - Taher Omer , Jawher (Diyala Journal of Medicine, 2020)
Background: For the purpose of preoperative diagnosis of thyroid lesions, the Fine Needle Aspiration Cytology (FNAC) has now replaced many other conventional pathology tests. Objective: To know to what extent the FNAC results are accurate by correlating them with results of histopathology. Patients and Methods: In this retrospective study, ninety-four cases of thyroid gland lesions were collected from the Department of Histopathology at Rizgary Teaching Hospital, Erbil City, Iraq during the period of three years, from January 2015 to December 2017, and correlate their FNAC outcome with that of histopathology. Results: A total of 94 cases were included in this study, 70 cases (74%) were female. Fifty cases (53%) were between 21-40 years of age. FNAC and histopathological results were correspondent in 84 cases (89.4%). The most common thyroid gland lesion was nodular colloid goiter occurred in 72 cases (77%) as confirmed by histopathology. Conclusion: The FNAC is relatively safe, simple, and cost effective preoperative diagnostic tool for thyroid lesions. However, it has some limitations.